2008
DOI: 10.1161/circresaha.108.175158
|View full text |Cite
|
Sign up to set email alerts
|

The Stem Cell Movement

Abstract: Abstract-Stem or progenitor cell-based strategies to combat ischemic heart disease and myocardial infarction, whether autologous transplantation or stimulation of resident populations, not only require detailed insight into transdifferentiation potential and functional coupling, but the efficacy of this approach is underpinned by the need to induce appropriate migration and homing to the site of injury. This review focuses on existing insights into the trafficking of stem cells in the context of cardiac regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(114 citation statements)
references
References 143 publications
(160 reference statements)
1
110
0
3
Order By: Relevance
“…Stem cells may also be affected by ageing mechanisms and as a result may become functionally impaired (Sharpless and DePinho 2007). As such, the addition of stem cell populations into tissues (Smart and Riley 2008) after the removal of senescent cells is thus another strategy in need of research.…”
Section: Future Considerationsmentioning
confidence: 99%
“…Stem cells may also be affected by ageing mechanisms and as a result may become functionally impaired (Sharpless and DePinho 2007). As such, the addition of stem cell populations into tissues (Smart and Riley 2008) after the removal of senescent cells is thus another strategy in need of research.…”
Section: Future Considerationsmentioning
confidence: 99%
“…Collectively, cell proliferation and migration of cardiac c‐Kit + progenitor cells are an essential cellular function for the heart development53 and cardiac repair, in which cardiac stem/progenitor cells are required to migrate to the infarcted myocardial zone and proliferate 55, 56. The present study demonstrates that bradykinin‐induced Ca 2+ signalling via stimulating ER IP3R3 to release Ca 2+ followed by Ca 2+ influx through SOCE channel initiates Akt and ERK1/2 phosphorylation and cyclin D1 expression and promotes cell proliferation and migration, suggesting that bradykinin may be useful for preconditioning cardiac progenitor cells to promote myocardial repair.…”
Section: Discussionmentioning
confidence: 99%
“…These cells may be involved in immune responses, but may also secrete cytokines (Liu et al, 2009a,b), and may be involved in cell proliferation and differentiation, growth inhibition, apoptosis, chemotaxis, and voluntary movement (Wang et al, 2002;Ding et al, 2008;Toth et al, 2008;Yin et al, 2009). BMMSCs may also create a microenvironment for the proliferation and differentiation of bone marrow hematopoietic stem cells (Smart and Riley, 2008). A previous study showed that cytokines such as GM-CSF, IL-6, IL-7, IL-8, IL-11, IL-12, IL-14, and IL-15 secreted by BMMSCs can support the growth of hemopoietic progenitor cells (Deans and Moseley, 2000).…”
Section: Discussionmentioning
confidence: 99%